Respuesta :
Answer:
[tex]A) 7[/tex]
Step-by-step explanation:
[tex]-2x+4=2\left(4x-3\right)-3\left(-8+4x\right)[/tex]
[tex]2\left(4x-3\right)-3\left(-8+4x\right)[/tex]
[tex]2 (4x - 3)[/tex]
[tex]\longrightarrow8x-6[/tex]
[tex]\longrightarrow 8x-6-3\left(-8+4x\right)[/tex]
[tex]-3 (-8 + 4x)[/tex]
[tex]\longrightarrow 24-12x[/tex]
[tex]8x-6+24-12x[/tex]
Combine like terms:
[tex]8x-12x-6+24[/tex]
Add: [tex]8x-12x=-4x[/tex]
Add: [tex]-6+24=18[/tex]
[tex]\longrightarrow-2x+4=-4x+18[/tex]
Subtract 4 from both sides:
[tex]\longrightarrow-2x+4-4=-4x+18-4[/tex]
[tex]\longrightarrow-2x=-4x+14[/tex]
Add 4x to both sides:
[tex]\longrightarrow-2x+4x=-4x+14+4x[/tex]
[tex]\longrightarrow2x=14[/tex]
Divide both sides by 2:
[tex]\longrightarrow\frac{2x}{2}=\frac{14}{2}[/tex]
[tex]\longrightarrow x=7[/tex]
____________________________
OAmalOHopeO